2022
DOI: 10.3390/ijms23179627
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Periplasmic-Binding Protein YfeA of Glaesserella parasuis Induces the Secretion of Pro-Inflammatory Cytokines of Macrophages via MAPK and NF-κB Signaling through TLR2 and TLR4

Abstract: The YfeA gene, belonging to the well-conserved ABC (ATP-binding cassette) transport system Yfe, encodes the substrate-binding subunit of the iron, zinc, and manganese transport system in bacteria. As a potential vaccine candidate in Glaesserella parasuis, the functional mechanisms of YfeA in the infection process remain obscure. In this study, vaccination with YfeA effectively protected the C56BL6 mouse against the G. parasuis SC1401 challenge. Bioinformatics analysis suggests that YfeA is highly conserved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated that in piglets infected with G. parasuis , mononuclear phagocytes increase the gene expression levels of the inflammatory cytokines IL-6 , IL-8 , and IL-10 via the NF-κB signaling pathway [ 32 ]. G. parasuis infection also triggers the upregulation of inflammatory cytokines, IL-1α, IL-1β, IL-6, IL-8, and TNF-α, in porcine alveolar macrophages by activating NF-κB and MAPK signaling pathways [ 33 , 34 ]. Moreover, G. parasuis elevated the expression of pro-inflammatory cytokines IL-1β, IL-6, and TNF-α in mice through the P38 and JNK-MAPK signaling pathways [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that in piglets infected with G. parasuis , mononuclear phagocytes increase the gene expression levels of the inflammatory cytokines IL-6 , IL-8 , and IL-10 via the NF-κB signaling pathway [ 32 ]. G. parasuis infection also triggers the upregulation of inflammatory cytokines, IL-1α, IL-1β, IL-6, IL-8, and TNF-α, in porcine alveolar macrophages by activating NF-κB and MAPK signaling pathways [ 33 , 34 ]. Moreover, G. parasuis elevated the expression of pro-inflammatory cytokines IL-1β, IL-6, and TNF-α in mice through the P38 and JNK-MAPK signaling pathways [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Western blotting assay was performed as described previously to detect the claudin-1 and occludin expression levels [49]. PK15 cells were plated into 6-well plates at a density of a 1 × 10 6 cells/well and stimulated with EspP2 (50 µg mL −1 ) for different lengths of time.…”
Section: Western Blottingmentioning
confidence: 99%